2022
DOI: 10.1007/jhep04(2022)113
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology of CP-even ALP

Abstract: Axion or axion-like particle (ALP) has been usually considered as a CP-odd Nambu-Goldstone boson (NGB) from the spontaneous breakdown of a global U(1) symmetry. In this paper, we point out that the NGB behaves as a CP-even particle coupled to the SM particles in a large class of simple (or perhaps the simplest) renormalizable models. We provide a first study of the collider phenomenology and cosmology of the CP-even ALP. In a natural parameter region, the CP-even ALP can be produced from the Higgs boson decay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 144 publications
0
6
0
Order By: Relevance
“…Interestingly, if c j , cx j have sizes of O(1) with generic O(1) CP phases, a behaves as a CPeven ALP [28]. This can be easily found that in any singlet scalar extension, the generic renormalizable potential has the form V full = V full (|H| 2 , ρ, a ).…”
Section: Renormalizable Model For a Generic Light Dark Sector 21 Modelmentioning
confidence: 98%
See 3 more Smart Citations
“…Interestingly, if c j , cx j have sizes of O(1) with generic O(1) CP phases, a behaves as a CPeven ALP [28]. This can be easily found that in any singlet scalar extension, the generic renormalizable potential has the form V full = V full (|H| 2 , ρ, a ).…”
Section: Renormalizable Model For a Generic Light Dark Sector 21 Modelmentioning
confidence: 98%
“…With the generic CP phases residing in c j , cx j , this CP-even ALP can mix with the SM-like and dark CP-even Higgs bosons in the low-energy effective theory and decay into the light components in the SM, like photons. The mixing between the SM-like Higgs boson and ALP can be estimated as [28]…”
Section: Renormalizable Model For a Generic Light Dark Sector 21 Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, pNGB DM model is also studied under the freeze-in production scenario [19][20][21], which is an alternative paradigm that is capable to evade the stringent direct detection bound. The freeze-in production mechanism requires the DM candidate to feebly interact with the SM particles, so that DM never get into thermal equilibrium with the SM plasma.…”
Section: Introductionmentioning
confidence: 99%